Perancangan Sistem POS Dengan Memanfaatkan Code Igniter Sebagai Framework Berbasis Web (Studi Kasus : Warung Jus Khupi 7) - Saan, Muhammad Yasir; Dalimunthe, Yulia Agustina; Irawan, Dedy (Universitas Islam Negeri Sumatera Utara, 2023)
Sales made manually become a problem for entrepreneurs who move especially in the culinary field. The reason is that it is less effective and efficient because recording and sales sometimes experience things in the form of missed calculations made by a human as well as factors such as lost or damaged manual records. This is also experienced by Warung Jus Khupi 7 where the sales system is still using manual methods when processing data in sales transactions. The development of information technology becomes a point of solution to the problems that exist in the business of juice stalls Khupi 7 engaged in culinary, especially the sale of coffee than needed a system with a user interface in the form of Point of Sale applications that can provide convenience to business owners and workers in conducting sales transactions and data processing of goods and making reports. The results of this study are an implementation of the design of web-based point of sale applications with code igniter framework and selected programming languages on the web, namely PHP, MySQL, and UML that can make the process of sales transactions of goods data processing and report making more effective and efficient Keywords: Point Of Sale, PHP Web, Mysql, Code Igniter